Formation Of Titania Nanotubes And Its Application In Reducing Cr(Vi) - Rahman, Intan Nur Izati Abdul (Universiti Sains Malaysia, 2017)
Cr(VI) is a toxic heavy metal which has been classified as carcinogenic to humans. The industrial sources of Cr(VI) include alloy and steel manufacturing, metal finishing, and leather tanning. This study investigated the applicability of TiO2 nanotubes (TNTs) for the removal of Cr(VI) from aqueous solution. The TNTs were synthesized by anodization technique in three different electrolytes which are Ethylene Glycol/NH4F, Glycerol/NH4F, and Na2SO4/NH4F at optimized times and voltages. The TNTs formation were then characterized by Field Emission Scanning Electron Microscope (FESEM), XRay Diffraction (XRD), Transmission Electron Microscope (TEM), and Fourier Transform Infrared (FTIR). Two main parameters were investigated which were the effects of anodization time and the effect of anodization voltage to the formation of TNTs with similar length but with different diameter in different electrolytes. The optimum sample defined by TNTs with length ~ 2  0.5 m were formed by anodization in Ethylene Glycol/NH4F for 60V in 30 minutes, Glycerol/NH4F for 40V in 12 hours, and Na2SO4/NH4F for 20V in 90 minutes. The samples were then being annealed at 400oC for three hours in air to form crystalline structure of the TNTs and in N2 gas to get the Ndoped TNTs. The annealed samples undergo XRD and FTIR characterization to confirm the crystallinity of TNTs formed. Then, the optimized samples that were annealed in air and N2 gas along with as anodized samples were tested for their photocatalytic ability under sunlight and UV light for two hours. The photocatalytic results were obtained by UV-VIS spectroscopy and the data of Ct/Co versus time were plotted.